Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Miftah Putra Mandiri Grup - Aditya Cikal Bagakara; Elmira Siska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of work environment and work discipline on employee performance at PT. Miftah Putra Mandiri Group. The main problems faced are the conditions of the work environment that are not conducive and the low level of discipline, which has a negative impact on employee performance. The method used in this study is a quantitative approach with an associative design. The population studied was all employees of PT. Miftah Putra Mandiri Group which totals 53 people, and all employees are used as samples using saturated sampling techniques. Data collection was carried out through the distribution of questionnaires using the Likert scale. The data obtained were analyzed using SPSS version 25, by conducting validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and determination coefficient. The results of the study show that both work environment variables and work discipline partially or simultaneously have a significant influence on employee performance. The t-test showed a significance value of 0.000 for both variables, which was smaller than 0.05, while the F-test yielded an Fcal value of 66.745 with a significance of 0.000. A determination coefficient (R²) of 0.723 indicates that 72.3% of the variation in employee performance can be explained by both variables. These findings affirm the importance of creating a comfortable work environment and improving work discipline as a key factor in improving employee performance in the company.